DETERMINATION OF VALUE CONTENT OF EDUCATION PROGRAMS DESIGNATED BY PRESCHOOL TEACHERS - Özkan SAPSAĞLAM; Esra ÖMEROĞLU (International Journal of Eurasia Social Sciences, 2015)
The present study aims to determine level of value included in the education programs applied by preschool teachers. Whereas the research is a case study designated in qualitative research pattern, homothetic sampling technic, which is type of purposeful sampling method, was utilized in determining study group. The study group is consisted of 35 preschool teachers who include values education in their education activities. Collected data within the scope of the research were analyzed by means of descriptive analysis. At the end of the research, it was determined that majority of teachers (83%) implement value education activity in every week; that respect (30%), honesty (30%), benevolence (30%) and responsibility (27%) were the values most frequently included in studies; that drama (50%), Turkish (47%) and game (33%) were the activity types which are most frequently included in values education activities; that computer (63%), story book (60%) and materials prepared by teacher (37%) were used more frequently; that teachers think that value teaching supports all development areas of children (86%); that majority of teachers (83%) allow participation of family in some activities; that they view pre-school education program (2013) is partly sufficient in terms of value education (43%); that majority of teachers (66%) do not participate in any scientific activity or education activity regarding value education; and that they consider themselves partly sufficient for giving value education (60%).